Spall behaviour of single crystal aluminium at three principal orientations - Owen,GD; Chapman,DJ; Whiteman,G; Stirk,SM; Millett,JCF; Johnson,S (Journal of Applied Physics, 2017)
A series of plate impact experiments have been conducted to study the spall strength of the three principal crystallographic orientations of single crystal aluminium ([100], [110] and, [111]) and ultra-pure polycrystalline aluminium. The samples have been shock loaded at two impact stresses (4 GPa and 10 GPa). Significant differences have been observed in the elastic behaviour, the pullback velocities, and the general shape of the wave profiles, which can be accounted for by considerations of the microscale homogeneity, the dislocation density, and the absence of grain boundaries in the single crystal materials. The data have shown that there is a consistent order of spall strength measured for the four sample materials. The [111] orientation has the largest spall strength and elastic limit, followed closely by [110], [100], and then the polycrystalline material. This order is consistent with both quasi-static data and geometrical consideration of Schmid factors.